Dampak Penggunaan Gadget Terhadap Penurunan Tajam Penghilatan Pada Siswa Smp N 8 Padang - Ermi Yusfita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The impact of the use of gadgets on the decline in sharp vision is most evident in the lack of focus in learning such as the distraction of students' attention on games, just checking social media, thus causing academic achievement to decline, and creativity is reduced. The purpose of the study was to determine the impact of gadget use on decreased sharp vision in SMPN 8 Padang students and to find out how to overcome excessive gadget use on decreased sharp vision in SMPN 8 Padang students. This research method is descriptive quantitative. The subjects in this study were students of SMPN 8 Padang conducted on June 28-July 2024. Data were collected through questionnaires and research instruments using a check list. Based on the research, the respondents at SMPN 8 Padang were 30 students. The results showed that as many as 17 students with a percentage (56.7%) had the impact of gadget use. And as many as 13 students with a percentage (43.3%) who do not have the impact of gadget use then as many as 16 students with a percentage (53.3%) know how to overcome the use of gadgets and as many as 14 students with a percentage (46.7%) who do not know how to overcome gadgets. The suggestion in this study is for students to improve the way they use excessive gadgets and use anti-radiation glasses, often do outdoor activities in order to avoid the impact of gadget use on sharp vision decline and also immediately check their eyes to the optics or ophthalmologist.